Thermal Comfort and Cognitive Performance under Glass Facade Buildings - Ega Rizkiyah; Manik Mahachandra; Ratna Purwaningsih; Heru Prastawa; Wiwik Budiawan (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2023)
Glass is one of the most adaptable modern materials. However, the use of glass can have unfavorable effects such as glare, heat, and discomfort. This study focuses on the issue of designing contemporary glass buildings and facades in humid tropical environments to evaluate the thermal comfort of building occupants and assess its effects on the completion of cognitive tasks. The Wet-Bulb Globe Temperature (WBGT) parameter was used to measure thermal comfort, and the ASHRAE (American Society of Heating, Refrigerating, and Air-Conditioning Engineers) scale was used to assess thermal comfort perception. The Montreal Cognitive Assessment was used to assess eight female respondents’ cognitive abilities, and the cut-off point was 26. The WBGT has a temperature range of 25, 54°–28, 83°C, in terms of thermal sensation, 54% of respondents feel hot and 62% are uncomfortable. In the completion of cognitive tasks, 75% received a score of less than 26. The results show that there is an effect of thermal comfort on cognitive performance. Due to respondents feeling uncomfortable in high-rise buildings with glass facades, as well as with cognitive outcomes that are below the cut-off point, recommendations for improvement are needed to increase thermal comfort, such as double glass facades.